The widening of the north-south divide: Debt sustainability in a world weakened by COVID-19 - Sandra Bernardo; Maria Luísa Jacquinet; Fátima Rocha (Economies, 2023)
This research compares the global debt trends in the aftermath of the COVID-19 pandemic, focusing on economies that frame the North and South divide. The research centers on debt ratios, which serve as indicators of countries' ability to finance recovery and development projects. The study period runs from 2015 to 2022 and follows the IMF's country classification, which divides the world into advanced economies (AE) and emerging market and developing economies (EMDE). The research employs panel data regressions to assess three key debt ratios-external debt to Gross Domestic Product (GDP), external debt to exports, and public debt to GDP-against various pandemic-related indicators and control variables. The analysis provides three major contributions. Firstly, an examination of external and public debt burdens is conducted, showing that escalated external and public debt burdens in EMDE contrast with increasing public debt in AE, primarily due to fiscal stimulus. Secondly, it is argued that the ongoing pandemic has intensified the widening economic gap between the North (AE) and the south (EMDE). Thirdly, a review is presented of both orthodox and heterodox policies identified in existing literature that are considered capable of mitigating external vulnerabilities in EMDE. Findings highlight the critical need for multifaceted measures to address debt vulnerability and promote sustainable economic recovery in a post-pandemic world.
Keywords: 330; COVID-19; globalization; indebtedness; inequalities; north–south divide